Ants as food for Apennine brown bears. Issue 1 (1st January 2018) - Tosoni, E.; Mei, M.; Ciucci, P.
Abstract: The value of ants to bears is a topic of substantial relevance for the small and highly endangered population of Apennine brown bears ( Ursus arctos marsicanus ) in central Italy. Following a previous food-habit study (2006–2009) based on scat analysis, we used the same data set to further investigate patterns of ant consumption by Apennine bears at a greater taxonomic and temporal resolution. We observed a great diversity of ant species in bear scats, comprising 15 genera and > 42 species. Bears most frequently consumed ants living in open grassland and forest edges, belonging to five genera: Formica, Lasius, Tetramorium, Camponotus and Myrmica . Specifically, yellow Lasius spp., Serviformica spp., Lasius s. str. spp., and Tetramorium spp. were most represented in the bear diet, followed by Formica pratensis, Camponotus spp., Myrmica spp. and Formica sanguinea . Yellow Lasius spp. yielded the highest number of individuals per bear scat, outnumbering any other ant taxon. During the years of our study, ant consumption by bears peaked between June and July and corresponded to a higher occurrence of brood in the scats. Our results are useful to inform habitat management, especially in light of expected natural and anthropogenic changes. However, further investigation is necessary to unveil behavioural and ecological correlates of myrmecophagy in Apennine brown bears.